হৃদয়ে একাত্তর - কায়সার, পান্না (ঢাকা : আগামী প্রকাশনী, 1993)
Collective memoirs about the life of the martyred revolutionaries of the 1971 Bangladesh revolution.
In Bengali.
Keywords: Revolutionaries -- Bangladesh -- Biography; Martyrs -- Bangladesh -- Biography; Bangladesh -- History -- Revolution, 1971 -- Biography